Morphological and molecular analysis of the tropical hermit crab Calcinus vachoni (Decapoda, Diogenidae) and its potential association with colonial anemone - Jung,Jibom; Park,Joong-Ki (PeerJ, 2023)
Calcinus is the colorful hermit crab genus belonging to the family Diogenidae and is often found in coral reefs of the tropical Indo-West Pacific region, including southern Honshu, Japan, which is the northern limit of their occurrence. In the present study, we found C. vachoni for the first time in the intertidal zone of Jeju Island—the southernmost island of South Korea. We examined their morphology and provided a diagnosis of their morphological details with illustrations. In addition, the Korean Calcinus population was genetically characterized using mtDNA cox1 sequences and by placing them into three previously reported regional haplogroups. The phylogenetic tree from maximum likelihood analysis revealed that Korean C. vachoni is assigned to the C. vachoni haplogroups exclusively, one of the three well-supported mitochondrial haplogroups with distinct geographic ranges (i.e., C. vachoni, C. aff. vachoni Cooks, and C. aff. vachoni Mascarenes). This result provides new information on the species distribution of C.vachoni, extending their geographic range further north into the southern coast of Korea. In this study, we also first report the potential association of C. vachoni with their co-occurring colonial anemone species Palythoa aff. mutuki and dead coral head of Pocillopora species based on our on-site observation and a public coral collection database of Calcinus species. However, their ecological association with co-occurring coral species is putatively assumed for now and therefore has to be validated by compelling evidence from further field observation and experimental studies (i.e., whether the presence/absence of colonial anemones affects the behavior and survival of the hermit crabs).
Keywords: C. vachoni; mtDNA cox1; Genetic divergence; Cryptic lineages; Ecological association; Palythoa aff. mutuki